A retrospective assessment of the implementation of virtual medical physics educational initiatives using the consolidated framework for implementation research - Fedor, Noelle; Abrahamson, E. Axel; Weygand, Joseph (Frontiers in Medicine, 2025)
Global disparities in access to radiation medicine are driven not only by infrastructure deficits but also by shortages of trained medical physicists. To address these gaps, RAD-AID International implemented four virtual educational initiatives in Kenya, Guyana, and Türkiye, along with a global lecture series, each aimed at strengthening local capacity in medical physics. Implementing such programs across diverse low- and middle-income country (LMIC) contexts presents significant challenges, particularly with regard to adaptability, engagement, and sustainability. To evaluate these efforts, we applied the Consolidated Framework for Implementation Research (CFIR) and the CFIR Expert Recommendations for Implementing Change (ERIC) Matching Tool to retrospectively identify barriers and recommend strategies to strengthen future initiatives. Stakeholders across all programs consistently cited limited access to knowledge and information as a key barrier. In response, the ERIC strategy “Conduct Educational Meetings” was highly endorsed, with 79% of experts identifying it as a top recommendation. Additional barriers, such as adaptability, planning, and responsiveness to patient needs, were matched with strategies including promoting adaptability, developing formal implementation blueprints, and engaging patients and families. By linking CFIR constructs to concrete examples, this study demonstrates the utility of structured implementation frameworks in radiological education and underscores the need for contextual sensitivity in resource-limited settings.